Geopolitics in the search for the disappeared Malaysian Airlines Flight MH370. (2018) - Wong, Alfred
Malaysian Airlines Flight MH370 flying on a routine flight from Kuala Lumpur to Beijing disappeared in the early morning of 8 March, 2014. The last radar-tracked position of the aircraft was some 400 km off Penang Island. After nearly three years of oceanic search of the anticipated crash site of MH370 in the area off the western coast of Australia, absolutely nothing tangible has been found to date. In mid 2015, some debris of the missing aircraft were found off the coast of southeastern Africa. The origin of the recovered flotsam (of MH370) could have been almost anywhere in the western half of the Indian Ocean. The probable crash site might be better identified if the fundamentals of the causes of the crash were examined additionally from the viewpoint of prevailing geopolitics and social psychology of the pilots.